The Impact of Multidrug-Resistant Organisms on Outcomes in Patients With Diabetic Foot Infections. (6th May 2020) - Henig, Oryan; Pogue, Jason M; Martin, Emily; Hayat, Umar; Ja'ara, Mahmoud; Kilgore, Paul E; Cha, Raymond; Dhar, Sorab; Kaye, Keith S
Abstract: Background: Multidrug-resistant organisms (MDROs) are important diabetic foot infection (DFI) pathogens. This study evaluated the impact of DFIs associated with MDRO pathogens (DFI-MDRO) on clinical outcomes. Methods: Adults admitted to Detroit Medical Center from January 2012 to December 2015 with culture-positive DFI were included. Associations between outcomes and DFI-MDRO (evaluated as a single group that included methicillin-resistant Staphylococcus aureus [MRSA], vancomycin-resistant enterococci, Enterobacteriaceae resistant to third-generation cephalosporin [3GCR-EC], Acinetobacter baumannii, and Pseudomonas aeruginosa ) were analyzed. Outcomes included above- and below-knee lower extremity amputation (LEA), readmissions, and mortality within a year after DFI. A propensity score predicting the likelihood of having DFI-MDRO was computed by comparing patients with DFI-MDRO with patients with DFI with non-MDRO pathogens (DFI-non-MDRO). Using conditional logistic regression, DFI-MDRO was analyzed as an independent variable after patients in the MDRO and non-MDRO groups were matched by propensity score. Results: Six hundred forty-eight patients were included, with a mean age ± SD of 58.4 ± 13.7. Most patients in the cohort presented with chronic infection (75%). DFI-MDRO occurred in greater than one-half of the cohort (n = 364, 56%), and MRSA was the most common MDRO (n = 224, 62% of the DFI-MDRO group). In propensity-matched analyses, DFI-MDRO was not associated with 1-year LEA or readmissions, but was associated with recurrent DFI episodes (odds ratio, 2.1; 95% confidence interval, 1.38–3.21). Conclusions: DFI-MDRO was associated with a 2-fold increased risk of recurrent DFI compared with patients with DFI-non-MDRO.